Pengaruh Endorser Yoshiolo Terhadap Brand Image Word Division - Kamaluddin Rahmat (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
Word Division is a local shoe brand that uses endorsers in its promotion. One of the endorsers chosen was Yoshiolo but Yoshiolo was better known through promotional content for foreign brands. This study aims to determine the influence of Yoshiolo as an endorser of the Word Division brand image. This study uses this study using a survey approach using questionnaires as a basic data collection tool and generally uses statistical methods. The results of the analysis show that Yoshiolo as an endorser has a positive and significant influence on the Word Division brand image